A Facile Regioselective Synthesis of New Class of Cyclopent[b]indole dispiro heterocycles via1, 3‐Dipolar Cycloaddition protocol and in vitro Cytotoxic studies. Issue 9 (27th March 2017) - Satheeshkumar, Rajendran; Edatt, Lincy; Kumar, V. B. Sameer; Prasad, Karnam Jayarampillai Rajendra
Abstract: The construction of azomethine ylides in situ from acenaphthoquinone/isatin and secondary amino acids such as sarcosine and thiaproline with cyclopent[ b ]indole dipolarophilesin refluxing dioxane and methanol afforded novel class of cyclopent[ b ]indole dispiro heterocycles via 1, 3‐dipolar cycloaddition reaction. The regio and stereochemistry of formation of the final product was concertedly assigned by proton, carbon and 2D NMR techniques. Among the synthesized dispiroheterocyclic compounds4 &7 are found to show better cytotoxic activity against HeLa and MCF‐7 with structure activity relationship (SAR) studies. Abstract : The construction of azomethine ylides in situ from acenaphthoquinone/isatin and secondary amino acids such as sarcosine and thiaproline with cyclopent[ b ]indole dipolarophilesin refluxing dioxane and methanol afforded novel class of cyclopent[ b ]indole dispiro heterocycles via 1, 3‐dipolar cycloaddition reaction. The regio and stereochemistry of formation of the final product was concertedly assigned by proton, carbon and 2D NMR techniques. Among the synthesized dispiroheterocyclic compounds4 &7 are found to show better cytotoxic activity against HeLa and MCF‐7 with structure activity relationship (SAR) studies.